2012
DOI: 10.1186/1476-069x-11-34
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and morbidity study of petrochemical employees in a polluted site

Abstract: BackgroundThe area of Gela was included among the 57 Italian polluted sites of national interest for environmental remediation because of its widespread contamination from a petrochemical complex. The present study investigates mortality and morbidity of the cohort of Gela petrochemical workers with the aim of disentangling occupational from residential risk.MethodsMortality was assessed for 5,627 men hired from 1960, year of the plant start-up, to 1993; it was followed up for vital status in the period 1960–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…In contrast, Knox (1994) identified the number of childhood leukaemia incidences to increase by 26% if residing within 5 km of an oil refinery, or 25% for those within 1.25 km of a downstream facility. While the debate has stifled in the UK, interest has peaked in recent years across other European nations, particularly in France and Italy (Pasetto et al, 2012; Pascal et al, 2013; Bentayeb et al, 2015; Fazzo et al, 2016). A 25-year study of 20,327 French residents, identified an 8% increase in mortalities per 1 μg/m 3 increase in the annual average concentration of benzene, after adjusting for pollutants from non-industrial sources (Bentayeb et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Knox (1994) identified the number of childhood leukaemia incidences to increase by 26% if residing within 5 km of an oil refinery, or 25% for those within 1.25 km of a downstream facility. While the debate has stifled in the UK, interest has peaked in recent years across other European nations, particularly in France and Italy (Pasetto et al, 2012; Pascal et al, 2013; Bentayeb et al, 2015; Fazzo et al, 2016). A 25-year study of 20,327 French residents, identified an 8% increase in mortalities per 1 μg/m 3 increase in the annual average concentration of benzene, after adjusting for pollutants from non-industrial sources (Bentayeb et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, an analysis of 44 industrially contaminated sites showed an excess of deaths [ 16 ] and an analysis of 17 sites showed an increase in the incidence of cancer [ 17 ]. In the area surrounding a large oil refinery, thermoelectric power plant, and petrochemical plants in Gela, Italy, people are at a high risk of lung cancer, and non-malignant respiratory and genitourinary diseases [ 18 ]. In Taranto, close to a large steel plant, a refinery, the harbour, and waste dumps, an excess risk of total deaths, all kinds of cancers, lung cancer, and cardiovascular and respiratory diseases, both acute and chronic, have been reported [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies further adjusted ethnicity, socioeconomic levels (e.g., school levels, job collars categories, unemployment, number of family members, overcrowding, and ownership of dwellings), or study periods. Four studies had full score of nine stars [ 18 , 21 23 ]; two had 8 out of 9 stars [ 7 , 8 ]; and one study had seven out of nine stars [ 19 ] (see Additional file 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…First, the definition of exposure varied slightly between studies. Most studies defined the exposure based on the geographical locations or distances of residencies from PIC [ 7 , 8 , 19 , 21 23 ], while one study compared the exposed group and reference group by matching job categories in PIC and non-PIC towns [ 18 ]. Misclassification of exposure and non-exposure might exist and bias the pooled estimates towards the null.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation